Kepemimpinan Kepala Dinas KOPERINDAG Provinsi Gorontalo - hasrul arafa; Arianto Chanan; Abd Kiftir Albakir (Oikos Nomos: Jurnal Kajian Ekonomi dan Bisnis, 2020)
This study ained to analyze the influence of leadership style and the availability of facilities on the performance of employees at the coopertives, SMEs, Industry, and Trade Office of Gorontalo Province. This quantitative research employed proportional random sampling as the sampling technique. From a population of 117 people, this study attained 31 people as samples. The data was abtained from a research questionnaire and processed using Microsoft excel program and SPSS statistics. The findings of the study showed that: 1) Pertially, the leadership style had positive effect an employee performance with an average score of 3.91. this indicated that the leadership style applied in the aforementioned area was a Democratic Leadership Style. 2) Pertially, the work facilities had a positive influence on employee performance with an average value of 4.56. This, the existing office facilities at the research site were in very good criteria. 3) Jointly, the leadership style and facilities had an influence on employee performance by 29.6%.